Structures in Physics and Neuroscience: Structural Realism and the Unity of Science. - Beni, Majid Davoody; Northoff, Georg (Axiomathes: Global Philosophy, 2021)
We offer to extend structural realism into the field of mind and brain studies. The naturalised metaphysics of structural realism has been defined in terms of unification of sciences. The unification program has been carried out nicely in fields of Quantum Mechanics and General Relativity. But for the structural realist metaphysics to receive a recommendation, the unification program needs to be extended to the fields of especial sciences. Our aim in the paper is twofold. On the one hand, we present a structural realist theory of the brain that is well-supported by the best theories of computational neurosciences. On the other hand, and at the same time, we provide further reason for being optimistic about the structural realism metaphysical claim which is based on the idea of unification in sciences.